Teaching Arabic language skills to non-specialist university students between the acquisition of basic skills and the mastery of the skill (Romano-arabica, 2025)
This study aims to know the Feasibility of the used way in the study of the skills of the Arabic language, and the perception of the optimum in the teaching; Where the viewer notices the emergence of the elements of the language, especially the grammar rules in the description of the skills of the Arabic language and its goals.This study answers the question: Is the method followed in teaching the Arabic language skills course based on choosing an element or a group of linguistic elements from among the language systems and their branches (phonology, morphology, grammar, lexicography, and semantics) useful in developing the student’s skills and linguistic abilities in reading, writing, speaking, and listening?The question branches into a sub-questions, such as: Is the most important thing in teaching this course the branches of language, especially grammar, or its skills? What is the benefit of choosing the course vocabulary to access lectures, activities and exercises? How can we benefit from illustrative means and putting students in practical situations in enabling these students to express themselves and discover the mistakes they make, such as giving a speech, holding a dialogue, managing a conversation, or writing an article?The student does not need more than the amount that helps him to master the skill from grammar. Therefore, he must enhance his appreciation of the language and knowledge of its culture, and train himself to read its texts and write in it professionally and functionally or artistically and creatively.